In-situ visualization and structure optimization of the flow channel of proton exchange membrane fuel cells - Qin, Zhengguo; Liu, Yuanyuan; Tongsh, Chasen; Bao, Zhiming; Li, Hongtao; Wu, Kangcheng; Deng, Zhe; Qin, Bowen; Du, Qing; Jiao, Kui (Frontiers in Energy Research, 2024)
The flow field serves as an important component of proton exchange membrane fuel cells (PEMFCs) for maintaining the hydration of the membrane and discharge of excessive water. In this study, a transparent polycarbonate plate was used as the cathode end plate of the PEMFC. The water management capacity of the PEMFCs with different cathode flow fields was evaluated. The movement and evolution patterns of water droplets, film, and columns in different flow fields were analyzed. The results show that liquid water is discharged faster as the cross-section of the flow channel becomes smaller. The performance of the PEMFC with a partially-narrowed flow field is higher due to better water management capacity and forced convection of gas reactant. Liquid water exists mostly in the form of liquid columns in the parallel flow channel, damaging the uniformity of gas distribution. The wavy flow field is likely to be flooded due to the difference of water movement velocity in different channel regions. In addition, a volume of fluid (VOF) model was developed to quantitatively evaluate the water management performance of each type of flow field. The water movement patterns in the different flow channels were concluded. This study provided real-time observations of water movement in the flow channel, revealing a correlation between water management capabilities and the performance of the PEMFC.